Wangari Maathai: Righteous Leader of Environmental and Social Change - Jennifer L. Kushner (Adult Education Research Conference, 2009)
This Africentric historical inquiry introduces Wangari Maathai, 2004 Nobel Peace Prize recipient, as a visionary adult educator and leader of the liberatory environmental movement known as The Green Belt Movement. The study describes Maathai’s philosophy and how it informed her leadership of adult education for environmental, political, and social change.